Amalarius of Metz at the Court of Leo V: A Note on Imperial Ceremonial - Basić, Ivan (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
In 813/814 a Frankish embassy led by Amalarius of Metz arrived at the court of Leo V in Constantinople. An account (Versus marini) written by Amalarius not long afterwards described the meeting held during the official audience. The words spoken to Amalarius by the emperor are analyzed and found to be the conventional formula prescribed by the Byzantine ambassadorial protocol as evidenced by the Book of Ceremonies and other texts.